Surface and Colloid Science 2004
DOI: 10.1007/b97092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of silica-coated magnetic nanoparticles

Abstract: The present work reports on the synthesis and properties of magnetic nanoparticles based on magnetite coated by a silica layer.A series of conditions was tested to allow the synthesis of the nanoparticles, usually performed in an aqueous medium, and could be efficiently coupled with the silica sol-gel process. The resulting particles were characterized by means of X-ray diffraction, transmission electron microscopy associated with electron energy loss spectra and electron spectroscopy imaging, Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…The same peaks were observed in the both the bare and silica-coated nanoparticle XRD patterns, indicating retention of the crystalline spinel ferrite core structure during the silica-coating process. The broad peak from 2θ = 20 • to 30 • was consistent with an amorphous silica phase in the shell of the SiMNPs [39].…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 60%
“…The same peaks were observed in the both the bare and silica-coated nanoparticle XRD patterns, indicating retention of the crystalline spinel ferrite core structure during the silica-coating process. The broad peak from 2θ = 20 • to 30 • was consistent with an amorphous silica phase in the shell of the SiMNPs [39].…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 60%
“…We were first examining the different polarities of alcohol that is essential in determining the size distribution and morphology of the nanoclusters. Haddad et al had reported that the volume ratio of solvent-water plays an important role in determining the shape of silica-coated magnetite nanoparticles [26]. They found that low water volume will prevent rapid hydrolysis and condensation of TEOS.…”
Section: Preparation Magnetite Nanoclusters Coated With Silicamentioning
confidence: 98%
“…in silica since the latter can be readily functionalised to impart the protective shell [13,14]. We recently reported the in situ as well as the post-modification of MNP with polyelectrolytes, without the need for encapsulation in silica [15,16].…”
Section: Introductionmentioning
confidence: 99%